Year of Expanding into Circulating Biomarkers - Jia, Shidong (J Circ Biomark, 2015)
This editorial article summarizes the achievements and current challenges for the Journal of Circulating Biomarkers (JCB) regarding a more strategic approach to branding and attracting a high quality variety of articles. More emphasis is placed on fostering engagement with academic and industry sources operating at the cutting-edge of translational technologies applied to the field of circulating biomarkers (interface between extracellular vesicles including exosomes and microvesicles, circulating tumour cells, cell-free circulating DNA and circulating protein markers) and with those in the investment arena seeking and providing private funding for this area of research.